Africa Region Tourism Strategy : Transformation through Tourism - Harnessing Tourism for Growth and Improved Livelihoods - World Bank (Washington, DC, 2013)
This paper presents the strategy vision for Africa of promoting tourism. The strategy relies on four pillars: policy reforms, capacity building, private sector linkages, and product competitiveness. Working closely with client countries, implementation of the Africa Region Tourism Strategy, will focus interventions in these four areas in order to address the persistent constraints to the growth of tourism in Africa. Combined, these interventions will enable high-demand tourism products to compete in the global marketplace. The approach is region-wide; it engages staff across the Bank's Africa Region. Implementation will be led by Africa Region s Finance and Private Sector Development Department (AFTFP). The World Bank Group support to the Africa tourism sector is currently 120 million US dollars. It could reach 500 US dollars million by 2015, generating as many as 300,000 direct formal jobs. The report examines the social, environmental, and economic risks associated with poorly managed tourism, and offers recommendations based on years of experience with tourism projects.This review has provided a snapshot of what Bank has been doing to support tourism development, and its alignment with national strategies in sub-Saharan Africa (SSA). The findings from this review are anticipated to facilitate future dialogue and negotiations among tourism stakeholders to increase support for tourism development in the region.